Evaluation of anti-hypertrophic potential of ethanolic extract of piper betle in isoproterenol induced cardiac hypertrophic rats - V. A. DOSS,; SWATHI MUTHUKUMAR,; DHARANIYAMBIGAI KUBERAPANDIAN, (International Journal of Pharma and Bio Sciences, 2019)
Piper betle (family – Piperaceae) contains two important phytochemicals namely hydroxychavicol (HC) and eugenol which are reported as cardio protective compounds. This study evaluates the cardioprotective (anti-hypertrophic) activity of ethanolic extract of the P. betle in isoproterenol administered male albino Wistar rats. Also the study attempts to investigate TSH as a risk marker for cardiac hypertrophy, For seven consecutive days, reference drug losartan (50 mg/kg BW, post oral) and ethanolic extract of P. betle (200 mg/kg BW, post oral) were simultaneously given to isoproterenol (ISO-10 mg/kg BW, i.p., 7 days) administered rats. Hypertrophic indices (HW/BW ratio) along with various biochemical estimations in serum such as glucose, total protein, albumin, lipid profile (total and HDL cholesterol, triglycerides), cardiac marker enzymes such as serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), lactate dehydrogenase (LDH), Enzymatic antioxidants namely superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and thyroid stimulating hormone (TSH) were performed followed by the histopathological analysis of heart. This study indicated statistically significant (P<0.05) increase in hypertrophic indices, glucose, protein, cholesterol, cardiac marker enzymes accompanied by decreased enzymatic antioxidants and TSH in ISO administered groups when compared to normal which all were reciprocated upon treatment with the plant extract. The study revealed the anti-hypertrophic potential of ethanolic extract of P. betle besides highlighting the impairment in TSH as risk factor for cardiac hypertrophy and the ability of betle leaves in intervening the condition.